Properties of lead zirconate-alumina 'nanocomposites' - Chompoonuch Puchmark (2018)
Microstructures, Vickers hardness and dielectric properties of PbZrO3ceramics with co-additions of 0.5-5 vol% Al2O3nanoparticles have been investigated. The additive inhibited grain growth, with average grain size decreasing from ∼13 μm for PbZrO3to ∼1 μm for the nanocomposites. The mode of fracture also changed, from predominantly inter-granular in PbZrO3to a mixed-mode of intra- and inter-granular fracture in the composite samples. Vickers hardness values increased from 2.9 GPa for PbZrO3to 4.1 GPa for the sample with 1 vol% Al2O3, but there was a more gradual increase for higher Al2O3contents. Plots of relative permittivity versus temperature indicated subtle differences which were attributed to a chemical reaction between the additive and matrix during sintering. X-ray powder diffraction showed that lead aluminium oxides were the principal products of this reaction. © 2006 Elsevier Ltd. All rights reserved.